Mechanistic analysis of bladder cancer suppression by brassicasterol in a rat model of N‐butyl‐N‐(4‐hydroxybutyl)nitrosamine‐induced bladder cancer. Issue 2 (8th June 2021) - Ikarashi, Nobutomo; Ono, Tetsuya; Hoshino, Motohiro; Toda, Takahiro; Yazawa, Yasuharu; Sugiyama, Kiyoshi
ABSTRACT: Aim: We previously clarified that the herbal medicine Polyporus Sclerotium, a constituent of Choreito, has an inhibitory effect on bladder carcinogenesis and that ergosterol is the active ingredient. In addition, we showed that this action of ergosterol may be caused by the metabolite brassicasterol. Here, we aimed to elucidate the detailed molecular mechanism by which brassicasterol inhibits bladder carcinogenesis. Methods: A rat model of bladder cancer was established by feeding rats N ‐butyl‐ N ‐(4‐hydroxybutyl)nitrosamine (BHBN) and sodium saccharin (SS). After intraperitoneal administration of brassicasterol to rats, the mRNA expression levels of cell cycle‐related genes (cyclin D1, c‐fos, and c‐jun), inflammation‐related genes (cyclooxygenase‐2; COX‐2), and androgen signal‐related genes (5α‐reductase type 1; 5α‐R1, 5α‐reductase type 2; 5α‐R2, and the androgen receptor; AR) in bladder epithelial cells were analyzed. Results: Brassicasterol significantly suppressed bladder carcinogenesis induced by BHBN and SS. The mRNA expression levels of cyclin D1 in bladder epithelial cells were significantly higher in the carcinogenesis group than in the control group. Additionally, the expression levels of c‐fos and c‐jun, constituents of the transcription factor activator protein‐1 (AP‐1) upstream of cyclin D1, were significantly increased in the carcinogenesis group compared with the control group. Moreover, the expression levels of COX‐2, 5α‐R1, 5α‐R2, and AR were significantly higher in the carcinogenesis group. In contrast, in rats treated with brassicasterol, the increases in the expression levels of these molecules were significantly suppressed. Conclusion: We clarified that brassicasterol suppresses bladder carcinogenesis by acting on cell cycle‐related signaling, inflammation‐related signaling, and androgen signaling via multiple mechanisms.